Effective substrate emissivity during dew water condensation. (February 2022) - Trosseille, Joachim; Mongruel, Anne; Royon, Laurent; Beysens, Daniel
Highlights: Water condensation on a substrate considerably modifies the substrate emissivity. A substrate-dependant transient regime initiates water condensation. After a transient regime, substrates exhibit emissivity close to water emissivity. During water condensation, substrate emissivity depends on water wetting properties. Graphical abstract: Abstract: Dew water condensation is due to the radiative cooling of a surface and is hence promoted on surfaces with high emissivity in the IR spectrum. The search for surfaces with enhanced radiative properties is usually carried out without considering the contribution of water condensation. On a condensing substrate, however, water droplets can occupy more than 55 % of the surface. Given the high emissivity of water ( ∼ 0.98), condensed water is thus expected to modify the condensation efficiency. The present study aims to investigate the interplay between water condensation and mean surface emissivity. Radiative cooling experiments in a humid air environment are performed using two substrates of contrasted emissivities (0.88 and 0.05). Although the condensation yield is initially larger on the high emissivity substrate, after a transient the condensation rate appears essentially the same for both substrates. A simple geometrical model taking into account the surface wetting properties reveals, in addition to the expected effect of droplet surface coverage, the existence of a threshold in drop thickness where water droplets effectively contribute to the radiative cooling process. The results are of conceptual and practical importance and can be generalized to any process involving vapor condensation induced by radiative cooling.